Photochemical smog introduction and episode selection for the ground-level ozone in Hanoi, Vietnam - Dam, Duy An (VNU, 2014)
Ozone (O3) is a secondary pollutant formed in the atmosphere throughout a complex non-linear chemical reaction involving two classes of precursors: the reactive volatile organic compounds (VOCs) and the oxides of nitrogen (NOx) in the presence of sunlight. The rapid urbanization and industrialization in Vietnam have brought about high air pollutant emissions including the O3precursors. Ground level O3may already be high in large cities like Hanoi and Ho Chi Minh City. The O3episode is very important for scene of view of photochemical smog in Hanoi. Ozone episodes are selected on the days which have a high concentration that lasts for at least two daystime. During the episode selection, ozone concentrations larger than 46ppb were observed at two stations (the Lang and Lac Long Quan stations) in March. The maximum value of 74ppb was measured at the Lang station at 14:00 on March 3. This episode was observed in a common meteorological condition for this time of the year.